The Medical Genome Reference Bank contains whole genome and phenotype data of 2570 healthy elderly - Mark Pinese (Nature Portfolio, 2020)
Healthspan and healthy aging are areas of research with potential socioeconomic impact. Here, the authors present the Medical Genome Reference Bank (MGRB) which consist of over 4,000 individuals aged 70 years and older without a history of the major age-related diseases and report on results from whole-genome sequencing and association analyses.